THE INFLUENCE OF NUTRITION ON WOUND HEALING IN PATIENTS WITH POST-SURGICAL INCISIONSECTION CAESAREAN (Studies In Jombang District Hospitals Rose Room) - David Eka Saputra; Endang Yuswatiningsih; Dwi Prasetyaningati (STIKES Insan Cendekia Medika Jombang, 2014)
The phenomenon abstain from food is carried out by people of the City and District of Jombang thepuerperium. Thebehaviorcauseslack ofnutritionnecessaryforwoundhealingandwoundperiniumsectioncaesareanoperation.the purpose ofthis studywas todetermine the influenceof nutritiononwoundhealinginpatients with post-surgical incisionsectioncaesarean in District hospitals rose Room.Thisstudydesignusingthe analyticapproach cross-sectional.Populationin this study wereallpatientsin thepostsurgicalsection caesarean Rose RoomJombangDistrictHospitalswith a sampel of32respondentsandsamplingtechniques is purposive konsecutive sampling. Compilingthe note information by means ofaquestionnairetocheck thesheetdennutrientsforwound healing.Analyze itbyusing theSpearmanRanktestwithanerror rate ( α) = 0.05.The results showedthatgoodnutrition 22 (68,8%), caring staff 6 (18,7%), less 4 (12,5%). While theprocessofwound healing, the wound is healed 27 (84,4%), the wounddoes notheal 5 (15,6%). Analysisof test results,the p value< α (0.000 < 0,05), H1accepted.Conclusionisthere are significant the influenceofnutritiononwoundhealinginpatients with post-surgical incisionsection caesarean.Key Words : Section Caesarean, Process ofWound Healing, Influenceof Nutrition